Elaboração de material didático como ferramenta para aprimorar a coleta seletiva de resíduos sólidos urbanos no sudoeste do Paraná - Zenatti, Geovana Maria (2023)
This work is the result of a partnership between the Biological Sciences course at the Federal Technological University of Paraná (UTFPR), Dois Vizinhos Campus, through the author and her supervisor, and the company Recyclebr, which operates in the field of environmental consultancy in the municipality of Francisco Beltrão-PR. This company has been developing a project called "Recyclebr - Gestão e Sistematização de Resíduos Sólidos Urbanos Municipais" (Recyclebr - Management and Systematization of Municipal Solid Waste) to work on waste management in the state of Paraná, since many municipalities still don't have solid waste management policies in place, leading to a series of problems for the environment and public health. The partnership therefore focused on the development of two teaching materials by the author and her supervisor as tools for working on environmental education in favor of implementing efficient selective collection of MSW. These didactic materials correspond to an Educational Booklet and a Flyer, which were prepared based on the analysis of an already published diagnosis, applied in loco in a neighborhood located in the Municipality of Francisco Beltrão-PR. Through this diagnosis, it was possible to identify the residents' main difficulties and produce materials that were true to the local reality. These didactic-pedagogical tools were created on the Canva graphic design platform and cover, according to the specifics of each style, technical subjects backed up by environmental legislation, definitions and concepts, as well as guidelines for the main difficulties listed by residents during the selective collection process. These teaching materials, which are aimed at secondary school students, have met the objectives set by the partner company and, as a result of their instructive nature, will help to answer questions about the process of segregating and disposing of solid waste.